KUALITAS DAN MOTIVASI BERDAMPAK PADA PRODUKTIVITAS BANSOS PASCA ERA COVID-19 - Fadly, Rachmat; Wardhana, Ananto Krisna; Utomo, Kurniawan Prambudi; Lestiowati, Riris; Kamal, Fahmi (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
The purpose of this research is to find out how much influence each variable of quality and employee motivation has on the productivity of social assistance, using complete statistical tools and testing, while the research methodology uses quantitative research using quantitative research methods and conducting field research that conducted online and offline, using the self-administered questionnaires mode method, namely distributing questionnaires directly to respondents to social service employees and social assistants and Beneficiary Families (KPM) with 40 respondents, while the results of the study show the quality and motivation of employees in social assistance productivity. shows a significant positive relationship for each variable, and the productivity of employees of both the Social Service for more right on target. Keywords: Quality, Motivation, Social, Assistance, Productivity